Survival and outcome of total elbow arthroplasty for distal humeral fracture at long term follow-up. - Schiavi, Paolo; Pogliacomi, Francesco; Garzia, Alice; Valenti, Piergiulio; Ceccarelii, Francesco; Calderazzi, Filippo (Acta Biomedica Atenei Parmensis, 2020)
Background Total elbow arthroplasty is an accepted procedure for the treatment of acute comminuted distal humeral fractures in elderly. Few long-term outcomes are available. The purpose of this study was to examine long-term clinical and radiological outcomes of prosthesis performed (January 2002-June 2015) for complex intra- fractures of the distal humerus (AO/C) in patients older than 65 years with low functional demands. Materials and Methods Further inclusion criteria were: the availability of a clinical and radiological follow-up of minimum 5 years and pattern of closed fracture. Demographic data and characteristics of patients were collected. All patients were clinically and radiographically assessed after 2 and 5 years from surgery. Results Twelve patients were included with complete available data. The mean follow-up was 7.6 years. Five patients reported a worsening of the elbow functionality through the follow-ups. Five subjects had complications. There were no cases of revision surgery. The quality of fixation showed a progressive worsening with increase of radiolucency both on humeral and ulnar side. The recorded MEPS showed no correlation with the grade of periprosthetic osteolysis. Polyethylene bushing wear was scored of grade 2 in one subject who had showed type 4 Morrey radiolucency. Discussion and Conclusions Total elbow arthroplasty is an effective and reliable procedure for comminuted fractures of the distal humerus in elderly, although the incidence of complications can not be considered as negligible. For the majority of these patients, a well-performed implant will give them a well-functioning elbow for their remaining life.